Parental Preferences about Policy Options Regarding Disclosure of Incidental Genetic Findings in Newborn Screening: Using Videos and the Internet to Educate and Obtain Input - Michael H. Farrell; Katherine E. Mooney; Anita Laxova; Philip M. Farrell (MDPI AG, 2022)
Our objective was to develop and test a new approach to obtaining parental policy guidance about disclosure of incidental findings of newborn screening for cystic fibrosis (CF), including heterozygote carrier status and the conditions known as CFTR-related metabolic syndrome (CRMS) and/or cystic fibrosis screen positive inconclusive diagnosis, CFSPID. The participants were parents of infants up to 6 months old recruited from maternity hospitals/clinics, parent education classes and stores selling baby products. Data were collected using an anonymous, one-time Internet-based survey. The survey introduced two scenarios using novel, animated videos. Parents were asked to rank three potential disclosure policies-Fully Informed, Parents Decide, and Withholding Information. Regarding disclosure of information about Mild X (analogous to CRMS/CFSPID), 57% of respondents ranked Parents Decide as their top choice, while another 41% ranked the Fully Informed policy first. Similarly, when considering disclosure of information about Disease X (CF) carrier status, 50% and 43% gave top rankings to the Fully Informed and Parents Decide policies, respectively. Less than 8% ranked the Withholding Information policy first in either scenario. Data from value comparisons suggested that parents believed knowing everything was very important even if they became distressed. Likewise, parents preferred autonomy even if they became distressed. However, when there might not be enough time to learn everything, parents showed a slight preference for deferring decision-making. Because most parents strongly preferred the policies of full disclosure or making the decision, rather than the withholding option for NBS results, these results can inform disclosure policies in NBS programs, especially as next-generation sequencing increases incidental findings.